The Design of a Sustainable Urban Tourism Development Model for Karbala is based on Social, Cultural, and Religious Aspects of Karbala City: Perancangan Model Pengembangan Pariwisata Perkotaan yang Berkelanjutan untuk Karbala didasarkan pada Aspek Sosial, Budaya, dan Keagamaan Kota Karbala - Muhsin Mahdi Rebat Al-kanany (Indonesian Journal of Law and Economics Review, 2026)
General Background: Urban tourism faces increasing challenges related to climate change, overtourism, and sustainability pressures. Specific Background: The integration of cultural heritage, religious tourism, and community participation is increasingly recognized as a key pathway toward sustainable urban tourism development. Knowledge Gap: Despite extensive research, limited integration exists between urban tourism sustainability, cultural dimensions, and community-based approaches within a unified analytical framework. Aims: This study examines how community participation and cultural integration contribute to sustainable urban tourism development. Results: The findings indicate that sustainable tourism requires balancing environmental, social, and economic dimensions, with strong emphasis on stakeholder collaboration, cultural preservation, and adaptive urban planning strategies. Novelty: The study provides a comprehensive perspective by linking urban tourism sustainability with cultural and religious dimensions alongside community-based approaches. Implications: The results suggest that policymakers and stakeholders should prioritize inclusive planning, cultural preservation, and community engagement to support long-term sustainability in urban tourism systems. Keywords: Urban Tourism, Sustainable Tourism, Community Participation, Cultural Heritage, Religious Tourism Key Findings Highlights Stakeholder collaboration supports balanced tourism development Cultural preservation strengthens long-term destination viability Integrated planning addresses environmental and social challenges